2016
DOI: 10.1186/s12957-016-1013-3
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of postoperative elemental diet (Elental®) in elderly patients after gastrectomy

Abstract: BackgroundWe aimed to investigate the efficacy of postoperative early intervention with an elemental diet to reduce weight loss and enhance recovery after gastrectomy. Nutritional status and gastrointestinal immune function tend to worsen, and postoperative weight loss is inevitable in these patients; therefore, improvement in their postoperative condition is important, especially in gastric cancer patients aged ≥80 years.MethodsClinical outcomes and postoperative nutritional status were compared between 21 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 24 publications
2
8
1
Order By: Relevance
“…Furthermore, the association of low SMI at diagnosis with a poorer OS was assessed in more than 5600 GC patients [ 13 ]. After surgery, a majority of patients experience a significant weight loss during the first two months due to postoperative complications, poor nutrition, prolonged hospital stay, and deterioration of quality of life [ 39 , 40 ]. In this context, further prospective studies should evaluate whether preoperative changes in body composition can impact postoperative complications and quality of life.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the association of low SMI at diagnosis with a poorer OS was assessed in more than 5600 GC patients [ 13 ]. After surgery, a majority of patients experience a significant weight loss during the first two months due to postoperative complications, poor nutrition, prolonged hospital stay, and deterioration of quality of life [ 39 , 40 ]. In this context, further prospective studies should evaluate whether preoperative changes in body composition can impact postoperative complications and quality of life.…”
Section: Discussionmentioning
confidence: 99%
“…Ohkura et al evaluated the efficacy of postoperative early intervention with an elemental diet to reduce body weight loss in elderly patients with gastric cancer (≥80 years of age). They showed that early intervention with an elemental diet after distal gastrectomy was useful for reducing perioperative weight loss in elderly patients (23). However, they did not evaluate the lean body mass loss.…”
Section: Gradementioning
confidence: 99%
“…Propensity score matching was used to balance the two groups, but the results must be interpreted carefully. Second, there are various definitions of the elderly patient [ 16 , 29 ]. Currently, the Japanese Geriatrics Society has proposed to redefine the elderly as 75 years of age or older, and thus we adopted a threshold of 75 years [ 30 ].…”
Section: Discussionmentioning
confidence: 99%